Polyester resin, adhesive and laminate

The polyester resin, characterized by its high aromatic dicarboxylic acid content and specific alkylene oxide derivatives of bisphenols, addresses the challenges of poor heat sealing and solvent resistance, delivering enhanced performance on difficult-to-adhere substrates and in solvent-rich environments.

JP2025054508APending Publication Date: 2025-04-08UNITIKA LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163575
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing polyester resins struggle with poor heat sealing properties on substrates with untreated surfaces, such as rubber materials, and inadequate solvent resistance, especially against solvents with high resin solubility like ethyl acetate.

Method used

A polyester resin with a specific structure, containing 80 mol% or more of aromatic dicarboxylic acid and 5 to 40 mol% of alkylene oxide derivatives of bisphenols, with a glass transition temperature between -10 to 30°C and a weight change rate of 10% or less when immersed in ethyl acetate.

Benefits of technology

The described polyester resin achieves excellent heat sealing properties and superior solvent resistance, even on substrates with poor adhesion, and maintains a low weight change rate when exposed to solvents like ethyl acetate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054508000001
    Figure 2025054508000001
  • Figure 2025054508000002
    Figure 2025054508000002
  • Figure 2025054508000003
    Figure 2025054508000003
Patent Text Reader

Abstract

To provide a polyester resin excellent in heat sealing property even to such materials as an untreated surface of a PET base material or a synthetic rubber, and excellent in solvent resistance.SOLUTION: The polyester resin contains 80 mol% or more of an aromatic dicarboxylic acid in 100 mol% of acid components, and 5 to 40 mol% of alkylene oxide derivatives of bisphenols in 100 mol% of glycol components, in which a glass transition temperature is -10 to 30°C and a weight change rate is 10% or less against ethyl acetate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester resin, an adhesive, and a laminate that are excellent in heat sealability to a substrate and solvent resistance. [Background technology]

[0002] 2. Description of the Related Art Polyester resins have been widely used as film-forming resins dissolved in organic solvents in applications such as paints, inks, adhesives, and coating agents.

[0003] For example, Patent Document 1 proposes a coating agent in which a polyester resin having a specific composition is dissolved in an organic solvent as a coating composition that has excellent adhesion to PET substrates and good solvent resistance and heat resistance and can be used for surface modification of PET sheets and bottles, and as a printing primer for PET films and containers. Generally, a treatment such as corona treatment is performed to improve the adhesion of the substrate surface, but in recent years, substrates with untreated surfaces are desired from the viewpoint of productivity. In addition, substrates to which adhesives and the like do not easily adhere, such as rubber materials, are sometimes used depending on the application. When these substrates are heat-sealed using an adhesive, the heat-sealing properties may be poor. In addition, when used in applications in which the polyester resin is used in combination with an organic solvent, such as paint or adhesive, a polyester resin with better solvent resistance to solvents that have high resin solubility, such as ethyl acetate, is required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-240204 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a polyester resin which has a well-balanced and excellent heat sealability with respect to substrates that have not been surface-treated or substrates made of materials that are particularly difficult to adhere to, such as rubber materials, and which also has excellent solvent resistance to solvents that have high resin solubility. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems and have discovered that a polyester resin having a specific structure exhibits superior heat sealability to a substrate and also has superior solvent resistance, thereby arriving at the present invention.

[0007] That is, the gist of the present invention is as follows. (1) A polyester resin containing 80 mol % or more of an aromatic dicarboxylic acid in 100 mol % of an acid component and 5 to 40 mol % of an alkylene oxide derivative of a bisphenol in 100 mol % of a glycol component, the polyester resin having a glass transition temperature of -10 to 30°C and a weight change rate of 10% or less as measured by the following method. Weight change rate: In accordance with JIS K7114:2001, 3 g of pelletized polyester resin is immersed in 100 g of ethyl acetate and left to stand for 48 hours in an atmosphere at 25° C. After standing for 48 hours, the pellets are taken out, the ethyl acetate adhering to the pellets is wiped off, the pellets are weighed, and the weight change rate is calculated using the following formula. Weight change rate (%)=(|m2-m1| / m1)×100 m1: weight of pellet before soaking (g) m2: Weight of pellet after soaking (g) (2) The polyester resin of (1), wherein the alkylene oxide derivative of a bisphenol is an ethylene oxide adduct and / or a propylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane. (3) A polyester resin according to (1) or (2), in which the content of polyglycol having one or more side chains is 10 mol % or less out of 100 mol % of the glycol component. (4) A polyester resin according to any one of (1) to (3), which contains 40 to 80 mol % of tetraethylene glycol based on 100 mol % of the glycol component. (5) A polyester resin according to any one of (1) to (4), having a number average molecular weight of 10,000 to 50,000. (6) An adhesive containing any one of the polyester resins (1) to (5). (7) A laminate comprising an adhesive layer made of the adhesive of (6). Effect of the Invention

[0008] The polyester resin of the present invention can provide a coating material or adhesive that has excellent heat sealability even with substrates having poor adhesion, and has excellent solvent resistance to solvents that have high resin solubility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. The polyester resin of the present invention is a polyester resin containing 80 mol % or more of aromatic dicarboxylic acid in 100 mol % of acid component and 5 to 40 mol % of alkylene oxide derivative of bisphenol in 100 mol % of glycol component, and has a glass transition temperature of -10 to 30°C. The polyester resin of the present invention has a weight change rate of 10% or less as measured by the following method. Weight change rate: In accordance with JIS K7114:2001, 3 g of pelletized polyester resin is immersed in 100 g of ethyl acetate and left to stand for 48 hours in an atmosphere at 25° C. After standing for 48 hours, the pellets are taken out, the ethyl acetate adhering to the pellets is wiped off, the pellets are weighed, and the weight change rate is calculated using the following formula. Weight change rate (%)=(|m2-m1| / m1)×100 m1: weight of pellet before soaking (g) m2: Weight of pellet after soaking (g)

[0010] The polyester resin of the present invention is mainly composed of a dicarboxylic acid component and a glycol component.

[0011] In order to improve heat sealability, the polyester resin of the present invention needs to have a total aromatic dicarboxylic acid content of 80 mol% or more, preferably 85 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and most preferably 100 mol%, out of 100 mol% of the acid component. If the aromatic dicarboxylic acid content is less than 80 mol%, the heat sealability will be poor.

[0012] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, phthalic anhydride, 5-sodium sulfoisophthalic acid, 2,6-naphthalenedicarboxylic acid, 3-tert-butylisophthalic acid, diphenic acid, etc. Two or more of these aromatic dicarboxylic acids can be used in combination.

[0013] The acid component other than the aromatic dicarboxylic acid can be used without any particular limitation as long as it does not impair the characteristics of the present invention. Examples of such dicarboxylic acid components include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, succinic anhydride, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, eicosane diacid, and hydrogenated dimer acid, unsaturated aliphatic dicarboxylic acids such as fumaric acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, citraconic acid, citraconic anhydride, and dimer acid, and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 2,5-norbornenedicarboxylic acid and its anhydride, and tetrahydrophthalic acid and its anhydride.

[0014] The polyester resin of the present invention has improved adhesion to a substrate, excellent heat sealability, and excellent solvent resistance, so that it is necessary to contain 5 to 40 mol % of an alkylene oxide derivative of bisphenols in 100 mol % of the glycol component, preferably 5 to 35 mol %, more preferably 8 to 30 mol %, and even more preferably 10 to 20 mol %. If the alkylene oxide derivative of bisphenols is less than 5 mol %, the solvent resistance will be low, and if it exceeds 40 mol %, the heat sealability will be poor.

[0015] Examples of alkylene oxide derivatives of bisphenols include an ethylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane, a propylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane, an ethylene oxide adduct of bis[4-(hydroxyethoxy)phenyl]sulfone, etc. These glycol components may be used alone or in combination.

[0016] Examples of glycol components other than alkylene oxide derivatives of bisphenols include aliphatic glycols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, and 2-ethyl-2-butylpropanediol, alicyclic glycols such as 1,4-cyclohexanedimethanol and 1,3-cyclobutanedimethanol, and ether bond-containing glycols such as diethylene glycol, triethylene glycol, dipropylene glycol, polytetramethylene glycol, polyethylene glycol, and polypropylene glycol. These glycol components may be used alone or in combination. Among these, the inclusion of triethylene glycol is preferred since it can improve the solvent resistance and the heat sealability in a more balanced manner, and the content of triethylene glycol in 100 mol % of the glycol component is more preferably 40 to 80 mol %, even more preferably 50 to 80 mol %, and most preferably 55 to 75 mol %.

[0017] In addition, in order to further improve the solvent resistance of the glycol component, the content of glycols having one or more side chains, such as 1,2-propanediol, 2-methyl-1,3-propanediol, and neopentyl glycol, is preferably 10 mol % or less, more preferably 5 mol % or less, even more preferably 2 mol % or less, and most preferably 0 mol %, based on 100 mol % of the glycol component.

[0018] The polyester resin may contain a hydroxycarboxylic acid component within a range that does not impair the characteristics of the present invention. Examples of hydroxycarboxylic acids include 2-hydroxysebacic acid, 5-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, citric acid, isocitric acid, malic acid, 2-methyl-2-hydroxysuccinic acid, tartaric acid, tetrahydroxyadipic acid, ε-caprolactone, δ-valerolactone, γ-valerolactone, lactic acid, β-hydroxybutyric acid, p-hydroxybenzoic acid, and alkylene oxide adducts of 4-hydroxyphenylstearic acid. When a hydroxymonocarboxylic acid is used, its content is preferably 50 mol% or less, more preferably 40 mol% or less, and even more preferably 30 mol% or less, out of a total of 100 mol% of the constituent components.

[0019] The polyester resin may contain monocarboxylic acid and monoalcohol within the range that does not impair the characteristics of the present invention. When using monocarboxylic acid and monoalcohol, the content is preferably less than 1 mol%, more preferably less than 0.1 mol%, and even more preferably 0 mol% relative to 100 mol% of dicarboxylic acid component and glycol component, respectively. In general, when monocarboxylic acid and monoalcohol are charged before esterification reaction and polycondensation reaction is carried out, the extension of molecular chain is hindered, and as a result, the required molecular weight cannot be obtained. Therefore, it may be difficult to set the viscosity of the polyester resin within the range of the present invention.

[0020] Examples of monocarboxylic acids include benzoic acid, phenylacetic acid, lauric acid, palmitic acid, stearic acid, and oleic acid, and examples of monoalcohols include cetyl alcohol, decyl alcohol, lauryl alcohol, myristyl alcohol, octyl alcohol, and stearyl alcohol.

[0021] The polyester resin may contain a trifunctional or higher functional carboxylic acid or a trifunctional or higher functional alcohol, provided that the characteristics of the present invention are not impaired. When a trifunctional or higher functional carboxylic acid or a trifunctional or higher functional alcohol is charged before the esterification reaction, the content is preferably 5 mol% or less, more preferably 4 mol% or less, and even more preferably 3 mol% or less, based on 100 mol% of the dicarboxylic acid component or the glycol component, respectively.

[0022] Examples of trifunctional or higher functional carboxylic acids include trimellitic acid, benzophenone tetracarboxylic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, benzophenone tetracarboxylic acid anhydride, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tris(anhydrotrimellitate), and 1,2,3,4-butane tetracarboxylic acid. Examples of trifunctional or higher functional alcohols include glycerin, trimethylol ethane, trimethylol propane, and pentaerythritol.

[0023] To achieve excellent heat sealability and solvent resistance, the glass transition temperature of the polyester resin must be −10 to 30° C., and is preferably −8 to 27° C., more preferably −5 to 25° C., and even more preferably 5 to 25° C. If the glass transition temperature is less than −10° C., the solvent resistance decreases, and if the glass transition temperature exceeds 30° C., the heat sealability decreases.

[0024] The number average molecular weight of the polyester resin is preferably from 10,000 to 50,000, more preferably from 10,000 to 40,000, and even more preferably from 10,000 to 30,000, since the polyester resin tends to have excellent heat sealability.

[0025] The relative viscosity of the polyester resin is preferably 1.20 to 1.80, more preferably 1.30 to 1.70, and further preferably 1.40 to 1.60. The relative viscosity of the polyester resin refers to a value measured at 20°C using an Ubbelohde viscometer after dissolving the polyester resin in a mixed solvent of equal masses of phenol / 1,1,2,2-tetrachloroethane at a concentration of 1% by mass. In order to set the relative viscosity of the polyester resin within the above range, for example, the copolymer composition or molecular weight can be adjusted.

[0026] The acid value of the polyester resin is not particularly limited as long as it is within a range that does not impair the characteristics of the present invention, and is preferably 15 mgKOH / g or less, and more preferably 10 mgKOH / g or less.

[0027] There are no particular limitations on the hydroxyl value of the polyester resin as long as it is within a range that does not impair the characteristics of the present invention, and it is preferably 30 mgKOH / g or less, and more preferably 20 mgKOH / g or less.

[0028] The polyester resin of the present invention has excellent solvent resistance against solvents such as ethyl acetate that have high resin solubility. Specifically, the polyester resin has a weight change rate of 10% or less, preferably 7% or less, more preferably 5% or less, and even more preferably 3% or less, as measured by the above-mentioned method. A resin with poor solvent resistance has a large weight change rate due to dissolving or swelling in ethyl acetate, that is, a smaller value indicates better solvent resistance.

[0029] Next, an example of a method for producing a polyester resin will be described. The polyester resin used in the present invention can be produced by a known method using the above-mentioned monomers in combination. For example, all monomer components and / or their oligomers are reacted in an inert atmosphere to carry out an esterification reaction, followed by a polycondensation reaction in the presence of a polycondensation catalyst under reduced pressure until a desired molecular weight is reached, and then a trifunctional or higher carboxylic acid is added in an inert atmosphere to carry out a depolymerization reaction.

[0030] In the esterification reaction, the reaction temperature is preferably 200 to 280° C., and the reaction time is more preferably 2.5 to 10 hours, and further preferably 4 to 6 hours.

[0031] In the polycondensation reaction, the reaction temperature is preferably 200 to 280° C. The degree of reduced pressure is preferably 130 Pa or less. If the degree of reduced pressure is higher than 130 Pa, the polycondensation time may become longer. It is preferable to gradually reduce the pressure from atmospheric pressure to 130 Pa or less over 60 to 180 minutes.

[0032] The polycondensation catalyst is not particularly limited, but examples thereof include known metal compounds such as zinc acetate, antimony trioxide, tetra-n-butyl titanate, and n-butylhydroxytin oxo as well as organic sulfonic acid compounds. Examples of organic sulfonic acid compounds include benzenesulfonic acid, m- or p-benzenedisulfonic acid, 1,3,5-benzenetrisulfonic acid, o-, m- or p-sulfobenzoic acid, benzaldehyde-o-sulfonic acid, acetophenone-p-sulfonic acid, acetophenone-3,5-disulfonic acid, o-, m- or p-aminobenzenesulfonic acid, sulfanilic acid, 2-aminotoluene-3-sulfonic acid, phenylhydroxylamine-3-sulfonic acid, phenylhydrazine-3-sulfonic acid, 1-nitronaphthalene-3-sulfonic acid, thiophene, phenylsulfonic acid ... o-, m- or p-chlorobenzenesulfonic acid, o-, m- or p-bromobenzenesulfonic acid, o-, m- or p-nitrobenzenesulfonic acid, nitrobenzene-2,4-disulfonic acid, nitrobenzene-3,5-disulfonic acid, nitrobenzene-2,5-disulfonic acid, 2-nitrotoluene-5-sulfonic acid, 2-nitrotoluene-4-sulfonic acid, 2-nitrotoluene-6-sulfonic acid, 3-nitrotoluene-5-sulfonic acid, 4-nitrotoluene 2-nitro-m-xylene-4-sulfonic acid, 5-nitro-m-xylene-4-sulfonic acid, 3-nitro-p-xylene-2-sulfonic acid, 5-nitro-p-xylene-2-sulfonic acid, 6-nitro-p-xylene-2-sulfonic acid, 2,4-dinitrobenzenesulfonic acid, 3,5-dinitrobenzenesulfonic acid, o-, m- or p-fluorobenzenesulfonic acid, 4-chloro-3-methylbenzenesulfonic acid, 2-chloro-4-sulfonic acid, benzoic acid, 5-sulfosalicylic acid, 4-sulfophthalic acid, 2-sulfobenzoic anhydride, 3,4-dimethyl-2-sulfobenzoic anhydride, 4-methyl-2-sulfobenzoic anhydride, 5-methoxy-2-sulfobenzoic anhydride, 1-sulfonaphthoic anhydride, 8-sulfonaphthoic anhydride, 3,6-disulfophthalic anhydride, 4,6-disulfoisophthalic anhydride, 2,5-disulfoterephthalic anhydride, methanesulfonic acid, ethanesulfonic acid, methionic acid, cyclopentanesulfonic acid, 1,1-ethanedisulfonic acid, 1,2-ethanedisulfonic acid, 1,Examples of the sulfonic acid include 2-ethanedisulfonic anhydride, 3-propanedisulfonic acid, β-sulfopropionic acid, isethionic acid, dithioic acid, dithioic anhydride, 3-oxy-1-propanesulfonic acid, 2-chloroethanesulfonic acid, phenylmethanesulfonic acid, β-phenylethanesulfonic acid, α-phenylethanesulfonic acid, ammonium chlorosulfonate, methyl benzenesulfonate, ethyl p-toluenesulfonate, ethyl methanesulfonate, dimethyl 5-sulfosalicylate, and trimethyl 4-sulfophthalate, as well as their salts.

[0033] The amount of catalyst added is 0.1 to 20 × 10 per mole of dicarboxylic acid component from the viewpoint of adjusting the degree of polymerization and suppressing coloration. -4 It is preferable to use a molar ratio.

[0034] In the depolymerization reaction, the reaction temperature is preferably 160 to 280° C., more preferably 160 to 220° C., and the reaction time is preferably 0.5 to 5 hours.

[0035] The polyester resin of the present invention may also contain an antioxidant. Antioxidants include phosphoric acid, phosphoric acid esters, 2,2-thio-diethylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], pentaerythritol tetrakis[3-(3′,5′-di-tert-butyl-4′-hydroxyphenyl)propionic acid], n-octadecyl 3-(3′,5′-di-tert-butyl-4′-hydroxyphenyl)propionate, 3,3′,3″ ,5,5′,5″-hexa-tert-butyl-a,a′,a″-(mesitylene-2,4,6-triyl)tri-p-cresol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5- methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzene)isophthalic acid, triethyl glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di- tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5] Undecane, dioctyl thiodipropionate, didodecyl thiodipropionate, didodecyl stearyl thiodipropionate, distearyl thiodipropionate, dimyristyl thiodipropionate, didecyl thiodipropionate, didecyl thiodipropionate, didecil-β,β'-thiodibutyrate, distearyl-β,β'-thiodibutyrate, pentaerythritol-tetrakis(dodecyl thiopropionate), pentaerythritol-tetrakis(dodecyl thioacetate), pentaerythritol-tetrakis(dodecyl thioacetate), Examples of the phosphorus-based compounds include tetrakis(dodecylthiobutyrate), pentaerythritol-tetrakis(octadecylthiopropionate), pentaerythritol-tetrakis(laurylthiopropionate), dilauryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, ditridecyl 3,3'-thiodipropionate, and tetrakis[methylene-3-(dodecylthio)propionate], as well as sulfur-based compounds, hindered phenol compounds, and hindered amine compounds.

[0036] The polyester resin of the present invention may further contain other resins and optional additives within the range that does not impair the characteristics of the present invention. Examples of such additives include a curing agent, inorganic particles, other heat stabilizers, color pigments, etc.

[0037] Examples of the curing agent include amino resins such as urea resins, melamine resins, and benzoguanamine resins, polyfunctional epoxy compounds, polyfunctional isocyanate compounds and their various blocked isocyanate compounds, carbodiimide group-containing compounds, oxazoline group-containing polymers, and phenolic resins. One of these may be used, or two or more may be used in combination. By including a curing agent, the solvent resistance and heat sealability of the polyester resin can be further improved. The blending amount of the curing agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the polyester resin of the present invention.

[0038] The method of using the polyester resin of the present invention is not particularly limited, but may be to dissolve the resin in an organic solvent, apply the solution (hereinafter, sometimes abbreviated as adhesive solution) to a substrate by a known coating method, and dry to form a coating film. As the coater, for example, a bar coater, a comma coater, a die coater, a roll coater, a reverse roll coater, a gravure coater, a gravure reverse coater, a flow coater, etc. can be used. In the coating method using these coaters, the thickness of the adhesive layer can be arbitrarily controlled. In addition, the substrate may be coated with the adhesive layer by a multiple coating method. In this method, a layer made of the resin (hereinafter, sometimes abbreviated as adhesive layer) can be obtained, and a laminate with the substrate can be obtained.

[0039] The polyester resin of the present invention has the above-mentioned characteristics (excellent heat sealability and solvent resistance), and is therefore suitable for paints, inks, adhesives, coating agents, etc. In particular, it is suitable for use in combination with organic solvents such as paints and adhesives, and such paints and adhesives can be used, for example, for printing plates. EXAMPLES

[0040] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.

[0041] [1. Evaluation method] (1) Composition of polyester resin Using a high-resolution nuclear magnetic resonance spectrometer (manufactured by JEOL, ECA500 type NMR), 1 The resin composition was determined from the peak intensity of each copolymer component by H-NMR analysis. Resolution: 500MHz Solvent: Deuterated trifluoroacetic acid Temperature: 25℃ Also, 1 For resins containing constituent monomers for which no assignable or quantifiable peaks were observed in the H-NMR spectrum, the resins were subjected to methanol decomposition in a sealed tube at 230°C for 3 hours, and then quantitative analysis was performed by gas chromatography.

[0042] (2) Acid value and hydroxyl value of polyester resin (Acid value) 0.5 g of polyester resin was dissolved in 50 ml of water / dioxane = 10 / 1 (volume ratio) and titrated with KOH using cresol red as an indicator. The number of milligrams of KOH consumed for neutralization was converted into the acid value per gram of polyester resin.

[0043] (Hydroxyl value) 3 g of the sample was weighed out and dissolved in 50 ml of pyridine. 5 ml of a pyridine solution of acetic anhydride (12% (V / V)) was then added, and acetylation was carried out at 60°C for about 1 hour. 50 ml of 1,4-dioxane was then added, followed by a few drops of a mixed indicator of cresol red and thymol blue. The solution thus dissolved was titrated with a 0.5N-KOH methanol solution, and the hydroxyl value (eq / t) of the target substance was calculated from the difference with the titration amount of the blank test. However, when using the above method, there are cases where the sample does not dissolve sufficiently and precipitates. In that case, as mentioned above, 1 H-NMR measurement was carried out to determine the composition and the hydroxyl value.

[0044] (3) Relative Viscosity of Polyester Resin The polyester resin was dissolved in an equal mass mixed solvent of phenol / 1,1,2,2-tetrachloroethane at a concentration of 1% by mass, and the flow times of the sample solution and the solvent were measured at 20° C. using an Ubbelohde viscosity tube, and the relative viscosity was calculated using the following formula. Relative viscosity: ηrel=t / t0 t: Flow time of polyester resin solution t0: solvent flow time

[0045] (4) Number average molecular weight of polyester resin The number average molecular weight was determined by GPC analysis using the following apparatus and conditions, and calculated as polystyrene. Liquid delivery unit (Shimadzu Corporation, LC-10ADvp type) UV-Visible Spectrophotometer (Shimadzu Corporation, SPD-6AV) Detection wavelength: 254 nm Solvent: Tetrahydrofuran When the polyester resin was not soluble in tetrahydrofuran, the number average molecular weight was measured using hexafluoroisopropanol as the solvent.

[0046] (5) Glass transition temperature of polyester resin 10 mg of polyester resin was weighed out, and measurement was performed using an input compensation type differential scanning calorimeter (PerkinElmer, Diamond type DSC, detection range: -50°C to 200°C) at a heating rate of 10°C / min. The glass transition temperature was determined as the temperature at the intersection of a straight line extending the low-temperature side baseline to the high-temperature side in the obtained heating curve and a tangent drawn at the point where the gradient of the curve in the stepwise change part of the glass transition is maximum.

[0047] (6) Solvent resistance of polyester resin (weight change rate) According to JIS K7114:2001, 3 g of pellet-shaped polyester resin was immersed in 100 g of ethyl acetate and left to stand for 48 hours in an atmosphere at 25° C. After standing for 48 hours, the pellet was taken out, the ethyl acetate adhering to the pellet was wiped off, and the pellet was immediately weighed. The weight change rate was calculated using the following formula. Weight change rate (%)=(|m2-m1| / m1)×100 m1: weight of pellet before soaking (g) m2: Weight of pellet after soaking (g)

[0048] (7) Heat sealability (heat seal strength with untreated surface of PET substrate) 30 parts by mass of the polyester resin obtained by the method of the Preparation Example described later was charged into a solvent mixture of 35 parts by mass of toluene and 35 parts by mass of methyl ethyl ketone, and the polyester resin was dissolved to obtain a polyester resin solution with a solids concentration of 30% by mass. This resin solution was applied to the non-corona side of a PET film (manufactured by Unitika Ltd., thickness 100 μm) using a tabletop coating device (manufactured by Yasuda Seiki Co., Ltd., film applicator No. 542-AB type, bar coater attached) to coat the ink so that the film thickness after drying would be 2 μm. The ink was then dried in a hot air dryer at 100°C for 30 seconds to obtain a laminate with a polyester resin coating. The non-corona side of the PET film was placed on the polyester resin coating of the obtained laminate, and the upper and lower rolls were rotated at 80°C and a linear pressure of 20 N / cm. 2 The lamination was performed under conditions of 1.5 m / min and a speed of 1.5 m / min to prepare a laminate sheet. A 25 mm wide sample was prepared from the obtained laminate sheet, and a T-peel test was carried out at 20° C. to evaluate the heat sealability according to the following criteria. ◎:15N / 25mm or more ○: 10N / 25mm or more, less than 15N / 25mm △: 3N / 25mm or more, less than 10N / 25mm ×: Less than 3N / 25mm

[0049] (8) Heat sealability (strength of heat seal with synthetic rubber) In the same manner as in (7) above, a laminate having a polyester resin coating formed thereon was obtained. A 1 mm-thick synthetic rubber (styrene butadiene rubber, Asaprene 1205, manufactured by Asahi Kasei Corporation) was placed on the polyester resin coating of the obtained laminate, and the upper and lower rolls were rotated at 80°C and a linear pressure of 20 N / cm. 2 The lamination was performed under conditions of 1.5 m / min and a speed of 1.5 m / min to prepare a laminate sheet. A 25 mm wide sample was prepared from the obtained laminate sheet, and a 180° peel test was carried out at 20° C. to evaluate the heat sealability according to the following criteria. ◎:10N / 25mm or more ○: 5N / 25mm or more, less than 10N / 25mm △: 1N / 25mm or more, less than 5N / 25mm ×: Less than 1N / 25mm

[0050] [2. Raw materials] (I) Polyester resin According to the procedures of Preparation Examples 1 to 6, polyester resins (a1) to (a26) used in the examples and comparative examples were obtained.

[0051] Adjustment example 1 A mixture consisting of 2977g of terephthalic acid, 1134g of the ethylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane, 613g of ethylene glycol, and 2018g of triethylene glycol was heated in an autoclave at 260°C for 4 hours to carry out an esterification reaction. The ratio of the monomer components was terephthalic acid: ethylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane: ethylene glycol: triethylene glycol = 100:20:55:75 (molar ratio). Next, 23 g of antimony trioxide was added as a catalyst (4.4 x 10-4 moles per mole of the total of all acid components), 10 g of triethyl phosphate as an antioxidant, and 6.7 g of pentaerythritol tetrakis [3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionic acid] were added, and the temperature of the system was raised to 270°C, and the pressure of the system was gradually reduced to 13 Pa after 1.5 hours. The polycondensation reaction was continued under these conditions, and after 4 hours, the system was returned to normal pressure with nitrogen gas, and polyester resin (a1) was obtained. The charged composition is shown in Tables 1 and 2, and the composition and properties of the polyester resin are shown in Tables 3 and 4.

[0052] [Table 1]

[0053] [Table 2]

[0054] [Table 3]

[0055] [Table 4]

[0056] Preparation Examples 2 to 26 Polyester resins (a2) to (a26) were obtained in the same manner as for polyester resin (a1), except that the charged compositions were changed as shown in Tables 1 and 2. The results are shown in Tables 3 and 4.

[0057] The abbreviations in Tables 1 and 2 stand for the following: TPA: Terephthalic acid IPA: Isophthalic acid ADA: Adipic acid BAEO: Ethylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane BSEO: Bis[4-(hydroxyethoxy)phenyl]sulfone and ethylene oxide adduct EG: Ethylene glycol TEG: Triethylene glycol NPG: Neopentyl glycol 1,4-BD: 1,4-butanediol CHDM: Cyclohexanedimethanol

[0058] Example 1 Various evaluations were carried out using the polyester resin (a1) obtained in Preparation Example 1. The evaluation results are shown in Table 5.

[0059] [Table 5]

[0060] Examples 2 to 21, Comparative Examples 1 to 5 Various evaluations were performed in the same manner as in Example 1, except that the type of polyester resin was changed as shown in Tables 5 and 6. The evaluation results are shown in Tables 5 and 6.

[0061] [Table 6]

[0062] The polyester resins of the present invention in Examples 1 to 21 had excellent adhesion to the untreated surface of the PET substrate and to the surface of synthetic rubber, and therefore had an excellent balance of heat sealability, and further had excellent solvent resistance to ethyl acetate.

[0063] The polyester resin of Comparative Example 1 had a poor heat sealability because the content of aromatic dicarboxylic acid in 100 mol % of the acid component was less than 80 mol %. The polyester resin of Comparative Example 2 had poor solvent resistance because the alkylene oxide derivative of bisphenols was less than 5 mol % in 100 mol % of the glycol component. The polyester resin of Comparative Example 3 had poor heat sealability because the alkylene oxide derivative of bisphenols exceeded 40 mol % in 100 mol % of the glycol component. The polyester resin of Comparative Example 4 had a glass transition temperature of less than -10°C and was therefore poor in solvent resistance. The polyester resin of Comparative Example 5 had a glass transition temperature of more than 30° C., and therefore was poor in heat sealability.

Claims

1. The polyester resin contains 80 mol % or more of an aromatic dicarboxylic acid in 100 mol % of an acid component, and 5 to 40 mol % of an alkylene oxide derivative of a bisphenol in 100 mol % of a glycol component, the polyester resin having a glass transition temperature of -10 to 30°C and a weight change rate of 10% or less as measured by the following method. Weight change rate: In accordance with JIS K7114:2001, 3 g of pelletized polyester resin is immersed in 100 g of ethyl acetate and allowed to stand for 48 hours in an atmosphere at 25° C. After standing for 48 hours, the pellets are taken out, the adhering ethyl acetate is wiped off, the weight is measured, and the weight change rate is calculated by the following formula. Weight change rate (%) = (|m 2 -m 1 | / m 1 )×100 m 1 : weight of pellet before immersion (g) m 2 : Weight of pellet after immersion (g)

2. 2. The polyester resin according to claim 1, wherein the alkylene oxide derivative of a bisphenol is an ethylene oxide adduct and / or a propylene oxide adduct of 2,2-bis[4-(hydroxyethoxy)phenyl]propane.

3. 3. The polyester resin according to claim 1, wherein the content of glycols having one or more side chains is 10 mol % or less based on 100 mol % of the glycol component.

4. 3. The polyester resin according to claim 1, which contains 40 to 80 mol % of triethylene glycol in 100 mol % of the glycol component.

5. 3. The polyester resin according to claim 1, wherein the number average molecular weight is 10,000 to 50,000.

6. An adhesive comprising the polyester resin according to claim 1 or 2.

7. A laminate comprising an adhesive layer made of the adhesive according to claim 6.

Citation Information

Patent Citations

  • Coating composition

    JP1994240204A